Formulating and parameterizing the allocation of net primary productivity for modeling overmature stands in boreal forest ecosystems - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai (Ecological Modelling, 2006)

Land use change in Asia and the ecological consequences - Zhao, Shuqing; Peng, Changhui; Jiang, Hong; Tian, Dalun; Lei, Xiangdong; Zhou, Xiaolu (Ecological Research, 2006)
Abstract Viewed within a historical context, Asia has experienced dramatic land transformations, and currently more than 50% of Asian land area is under agriculture. The consequences of this transformation are manifold. Southeast Asia has the highest deforestation rate of any major tropical region. Many of the world's large rivers and lakes in Asia have been heavily degraded. About 11 of 19 world megacities with more than 10 million inhabitants are in Asia. These land use activities have resulted in substantial negative ecological consequences, including increased anthropogenic CO 2 emissions, deteriorated air and water quality, alteration of regional climate, an increase of disease and a loss of biodiversity. Although land use occurs at the local level, it has the potential to cause ecological impact across local, regional and global scales. Reducing the negative environmental impacts of land use change while maintaining economic viability and social acceptability is an major challenge for most developing countries in Asia.